Brugada syndrome: A comprehensive review of pathophysiological mechanisms and risk stratification strategies. (February 2020) - Li, Ka Hou Christien; Lee, Sharen; Yin, Chengye; Liu, Tong; Ngarmukos, Tachapong; Conte, Giulio; Yan, Gan-Xin; Sy, Raymond W.; Letsas, Konstantinos P.; Tse, Gary
Abstract: Brugada syndrome (BrS) is an inherited ion channel channelopathy predisposing to ventricular arrhythmias and sudden cardiac death. Originally believed to be predominantly associated with mutations in SCN5A encoding for the cardiac sodium channel, mutations of 18 genes other than SCN5A have been implicated in the pathogenesis of BrS to date. Diagnosis is based on the presence of a spontaneous or drug-induced coved-type ST segment elevation. The predominant electrophysiological mechanism underlying BrS remains disputed, commonly revolving around the three main hypotheses based on abnormal repolarization, depolarization or current-load match. Evidence from computational modelling, pre-clinical and clinical studies illustrates that molecular abnormalities found in BrS lead to alterations in excitation wavelength (λ), which ultimately elevates arrhythmic risk. A major challenge for clinicians in managing this condition is the difficulty in predicting the subset of patients who will suffer from life-threatening ventricular arrhythmic events. Several repolarization risk markers have been used thus far, but these neglect the contributions of conduction abnormalities in the form of slowing and dispersion. Indices incorporating both repolarization and conduction based on the concept of λ have recently been proposed. These may have better predictive values than the existing markers. Current treatment options include pharmacological therapy to reduce the occurrence of arrhythmic events or to abort these episodes, and interventions such as implantable cardioverter-defibrillator insertion or radiofrequency ablation of abnormal arrhythmic substrate.